2021
DOI: 10.1177/14651165211063770
|View full text |Cite
|
Sign up to set email alerts
|

United or divided in diversity? The heterogeneous effects of ethnic diversity on European and national identities

Abstract: In this article, we argue that the size and cultural proximity of immigrant populations in people's residential surroundings shape national and European identities. This means that the type of migrant population activates cultural threat perceptions and opportunities for contact to varying degrees. Geocoded survey data from the Netherlands suggests that large non-Western immigrant shares are associated with more exclusive national identities, while mixed contexts with Western and non-Western populations show m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…In this context where Euroscepticism continues to grow, our study contributes to understanding how politicians’ use of identity-related frames can promote or reduce ethnocultural NIR salience and the negative relationship this form of exclusive nationalism has with support for the EU. Notably, media exposure is not the only factor affecting NIR salience: other factors such as labour market position, employment status, educational level, or living close to culturally distant migrant groups were all found to increase the salience of more exclusive national identities (Foster and Frieden, 2021; Schraff and Sczepanski, 2022). Our study adds to this buoyant literature by highlighting how framing EU policies in assimilation terms fosters ethnocultural nationalism, thus contributing to explain why Euroscepticism grows aided, among other factors, by the increased use of assimilation frames in EU countries.…”
Section: Discussionmentioning
confidence: 99%
“…In this context where Euroscepticism continues to grow, our study contributes to understanding how politicians’ use of identity-related frames can promote or reduce ethnocultural NIR salience and the negative relationship this form of exclusive nationalism has with support for the EU. Notably, media exposure is not the only factor affecting NIR salience: other factors such as labour market position, employment status, educational level, or living close to culturally distant migrant groups were all found to increase the salience of more exclusive national identities (Foster and Frieden, 2021; Schraff and Sczepanski, 2022). Our study adds to this buoyant literature by highlighting how framing EU policies in assimilation terms fosters ethnocultural nationalism, thus contributing to explain why Euroscepticism grows aided, among other factors, by the increased use of assimilation frames in EU countries.…”
Section: Discussionmentioning
confidence: 99%
“…Not only cognitive experiences but also social interactions, including engagements with symbols and interactions with different social groups, play a crucial role in the development of political identities. Deutsch (1957) argued that transnational contacts and interactions contribute to the adoption of European identities, and subsequent research has shown that experiences such as participating in Erasmus programs and residing in diverse neighborhoods foster the growth of European identity (Kuhn, 2011; Schraff & Sczepanski, 2022; Stoeckel, 2016, but see Kuhn, 2012). Moreover, symbols representing the European Union and pro-European actions have been demonstrated to be related to the adoption of a European identity (Nicoli et al, 2020; Sczepanski, 2023a).…”
Section: The Development Of Political Identities In the Socio-structu...mentioning
confidence: 99%
“…The dependent variables in my study are European and national identity, which were measured independently of each other. This separate measurement is based on research indicating that these two identities do not necessarily trade off against each other (Schraff & Sczepanski, 2022) (see Appendix for differences in national identities and European identities among Remain, Leave, and undecided voters). To capture the nuances of European and national identity, I employed four different items based on the work of Huddy and Khatib (2007).…”
Section: Empirical Strategymentioning
confidence: 99%
“…The dependent variables in my study are European and national identity, measured independently from each other. The independent measurement of those identities is based on research that shows that these two identities do not form a trade-off (Schraff and Sczepanski, 2021) (see Appendix for differences in national identities and European identities between Remain, Leave and undecided voters). I use four different items to capture the nuances of European and national identity based on work by Huddy and Khatib (2007).…”
Section: Empirical Strategymentioning
confidence: 99%
“…Not only cognitive but also social experiences, such as interactions with other social groups and engagements with symbols of a political group, are important drivers for developing political identities. Based on Deutsch's (1957) notion that contact with different cultures enhances citizens' adoption of European identities, some research has shown that Erasmus stays as well as diverse neighbourhoods foster European identity growth (Kuhn, 2011;Schraff and Sczepanski, 2021;Stoeckel, 2016, whereas others present conflicting evidence for Erasmus Kuhn, 2012). In addition, symbols representing the European Union and actions in favour of the European Union have been shown to shape the adoption of a more European identity (Nicoli et al, 2020;Sczepanski, 2022a).…”
Section: Introductionmentioning
confidence: 99%